AUTENTIKASI DAGING AYAM SEGAR DARI KONTAMINASI DAGING BABI MENGGUNAKAN GEN CYT-B DENGAN ANALISIS DUPLEX- POLYMERASE CHAIN REACTION - Bayu Setya Hertanto; Rizky Aulia Fitra; Lilik Retna Kartikasari; Muhammad Cahyadi (Buletin Peternakan, 2017)
Halal is one of important aspects in consumer protection. Meat and processed meat products are food that should be controlled strictly because those are prone to be adulterated by pork contamination. Therefore, it is necessary to provide detection technique which is accurate, fast and cheap. The objective of this research was to identify the presence of impurities of pork meat on raw chicken meat using gene Cyt-b with duplex-PCR analysis. This research used six samples of raw chicken meat and raw pork. Raw chicken meat was bought from supermarkets in the city of Surakarta and raw pork was obtained from pig slaughterhouse. The percentage of raw pork contamination on raw chicken meat was designed as much as 1, 5, 10, and 25%, respectively. The DNA genome was isolated according to DNA isolation protocol from Genomic DNA Mini Kit. In addition, duplex-PCR was performed based on protocol of KAPA2G Fast Multiplex PCR kit. The data was descriptively analyzed by directly looking the DNA bands on the gel documentation apparatus. The result showed that specific DNA bands for chicken and pig were completely appeared on 1.5% of agarose gels. Duplex-PCR detect contamination of pork on raw meat of chicken at all contamination levels. This research proved that the duplex-PCR detect the contamination of pork until the level of 1%.